Formant analysis of vertebrate vocalizations: achievements, pitfalls, and promises - W. Tecumseh Fitch; Andrey Anikin; Katarzyna Pisanski; Daria Valente; David Reby (BMC Biology)
Abstract When applied to vertebrate vocalizations, source-filter theory, initially developed for human speech, has revolutionized our understanding of animal communication, resulting in major insights into the form and function of animal sounds. However, animal calls and human nonverbal vocalizations can differ qualitatively from human speech, often having more chaotic and higher-frequency sources, making formant measurement challenging. We review the considerable achievements of the “formant revolution” in animal vocal communication research, then highlight several important methodological problems in formant analysis. We offer concrete recommendations for effectively applying source-filter theory to non-speech vocalizations and discuss promising avenues for future research in this area. Brief Formants (vocal tract resonances) play key roles in animal communication, offering researchers exciting promise but also potential pitfalls.